Fecal Microbiota Transplantation Is Effective in Relieving Visceral Hypersensitivity in a Postinfectious Model - Bai, Tao (Biomed Res Int, 2018)
AIM: To investigate the effect of fecal microbiota transplantation on visceral hypersensitivity compared with Bifidobacterium longum. METHODS: Mice visceral hypersensitivity was induced by Trichinella spiralis. After 8 weeks, they were divided into three groups (controls, Bifidobacterium longum, and fecal microbiota transplantation) and were daily treated by gavage with 0.2 ml PBS, Bifidobacterium longum HB55020, or fecal microbiota for 7 days. Visceral hypersensitivity was tested with abdominal withdrawal reflex. Permeability of colon epithelium was assessed with Ussing chamber. RESULTS: After administration of Bifidobacterium longum, compared with mice in postinfectious group, mice had higher pain threshold (p < 0.05). After administration of fecal microbiota, compared with mice in postinfectious group, mice had higher pain threshold (p < 0.05). Fecal microbiota transplantation was as effective as Bifidobacterium in relieving visceral hypersensitivity. Administration of Bifidobacterium longum or fecal microbiota transplantation improved colon epithelium permeability. Expression of occluding-1 was increased. CONCLUSION: Manipulation of microbiota is effective in relieving visceral hypersensitivity. Fecal microbiota transplantation is as effective as Bifidobacterium longum administration.